Análise de dados e definição de indicadores para a regulação de usinas termelétricas dos sistemas isolados - CONDE, Cláudio Luciano da Rocha (Universidade Federal do Pará, 2017)
This thesis proposes an efficient and low cost monitoring system of electrical parameters and fuel consumption of thermal plants of the Brazilian isolated electrical systems, almost all located in the Amazon Region. These systems have many operational problems, usually related to the great distances and lack of data necessary to provide power quality and fuel consumption control. The analysis of the acquired data after the implantation of the considered system in four thermal plants in the State of Pará became possible, among other results, the development of an indicator (IMU) that can be used in the short and average planning studies. The viability of the proposed solution for the operative and regulatory control stimulated the development of a methodology to install monitoring systems all over the isolated systems of Brazil, included in a Brazilian Electricity Regulatory Agency (ANEEL) regulatory act.